THE DESIGN OF LEARNING THIS IN PHYSICAL EDUCATION CLASSES TEACHERS OF BASIC EDUCATION (Fiep Bulletin - online, 2017)
This article aims to present the design of this learning in teaching practice of physical education teachers of basic education who work in elementary school II and / or middle classes. Among the authors used for the theoretical foundation on the design of learning in Physical Education is Schmidt (2010); Magill (2000); Tani, (2013); Ugrinowitsch and Tani (2013) and Clark, (2013). The methodology was qualitative in view of hermeneutic phenomenological approach. The results presented indicate the learning concept of presence in the field of physical education focused on specific performance of motor skills by the students, with a focus on repeat with a view to automating the movement. Highlights the need to rethink the process of teaching and learning in class so that each student can become protagonist of their learning, giving way to other content learned in addition to the performance.